Steering of Vortices by Magnetic Field Tilting in Open Superconductor Nanotubes - Igor Bogush; Vladimir M. Fomin; Oleksandr V. Dobrovolskiy (Nanomaterials, 2024)
In planar superconductor thin films, the places of nucleation and arrangements of moving vortices are determined by structural defects. However, various applications of superconductors require reconfigurable steering of fluxons, which is hard to realize with geometrically predefined vortex pinning landscapes. Here, on the basis of the time-dependent Ginzburg–Landau equation, we present an approach for the steering of vortex chains and vortex jets in superconductor nanotubes containing a slit. The idea is based on the tilting of the magnetic field <semantics>B</semantics> at an angle <semantics>α</semantics> in the plane perpendicular to the axis of a nanotube carrying an azimuthal transport current. Namely, while at <semantics>α=0∘</semantics>, vortices move paraxially in opposite directions within each half-tube; an increase in <semantics>α</semantics> displaces the areas with the close-to-maximum normal component <semantics>|Bn|</semantics> to the close(opposite)-to-slit regions, giving rise to descending (ascending) branches in the induced-voltage frequency spectrum <semantics>fU(α)</semantics>. At lower B values, upon reaching the critical angle <semantics>αc</semantics>, the close-to-slit vortex chains disappear, yielding <semantics>fU</semantics> of the <semantics>nf1</semantics> type (<semantics>n≥1</semantics>: an integer; <semantics>f1</semantics>: the vortex nucleation frequency). At higher B values, <semantics>fU</semantics> is largely blurry because of multifurcations of vortex trajectories, leading to the coexistence of a vortex jet with two vortex chains at <semantics>α=90∘</semantics>. In addition to prospects for the tuning of GHz-frequency spectra and the steering of vortices as information bits, our findings lay the foundation for on-demand tuning of vortex arrangements in 3D superconductor membranes in tilted magnetic fields.